Molecular control of the band edge movement and the recombination process in donor-acceptor hemicyanine-sensitized solar cells - Karjule, Neeta; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (Journal of Physical Chemistry C, 2017)
The presence of downward shift in the band edge and the recombination reactions in the hemicyanine-sensitized solar cell reduces the open-circuit potential (V-oc) and the short-circuit current density (J(sc), which in turn decreases the dye cell performance. Choosing either an electrolyte possessing minimum overpotentials or a systematic dye design which can efficiently suppress the diffusion of charged species toward the TiO2 can improve the overall power conversion efficiency (PCE). Here, a series of donor acceptor (D-A) hemicyanine dyes were synthesized utilizing a planar heterotriangulene (HT) or triphenylamine (TPA) donor and alkyl-functionalized indolium carboxylic acid acceptor unit. By introducing strong HT donor instead of TPA, the photophysical, and electrochemical properties of D-A dyes are significantly modulated. The strong donor nature of HT and effective passivation of surface by hydrophobic alkyl chains close to the anchoring group for NC3 dye exhibits an average PCE of 4.34% with a V-oc of 0.416 V, J(sc) of 20.04 mA cm(-2), and fill factor (ff) of 52.03% under simulated AM 1.5G illumination (100 mW cm-2) without 3 alpha,7 alpha-adihydroxy-5 beta-cholic acid coadsorbent (CDCA). The intrinsic dipole of the hemicyanine dye and the presence of Li+ ions in iodide/triiodide redox couple without tert-butylpyridine (TBP) additive induces a downward shift in conduction band edge (E-CB) of TiO2. By rational molecular design, the extend of shift in E-CB is controlled and enhanced the V-oc. Electrochemical impedance spectroscopy (EIS) studies revealed the high charge transfer resistance (R-ct) and long lifetime (tau) of injected electrons in HT-based dyes than that of TPA derivatives, which provide insight into the passivation of Li+ and I- ions by current D-A dye design possessing alkyl functionalities to increase both the J(sc) and V-oc.